2022
DOI: 10.3390/ijms232315296
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Glutaminolysis as a Novel Strategy to Combat Cancer Stem Cells

Abstract: Rare subpopulations of cancer stem cells (CSCs) have the ability to self-renew and are the primary driving force behind cancer metastatic dissemination and the preeminent hurdle to cancer treatment. As opposed to differentiated, non-malignant tumor offspring, CSCs have sophisticated metabolic patterns that, depending on the kind of cancer, rely mostly on the oxidation of major fuel substrates such as glucose, glutamine, and fatty acids for survival. Glutaminolysis is a series of metabolic reactions that conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 149 publications
0
8
0
Order By: Relevance
“…Moreover, inhibition of Gln uptake decreased tumour growth and metastasis [ 36 ]. Glutaminolysis inhibition has generally reduced disease recurrence risk and metastases in several tumour entities [ 35 , 37 ]. Therefore, the influence of Gln on the clonogenic potential, migration, invasion, and adhesion was investigated within this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibition of Gln uptake decreased tumour growth and metastasis [ 36 ]. Glutaminolysis inhibition has generally reduced disease recurrence risk and metastases in several tumour entities [ 35 , 37 ]. Therefore, the influence of Gln on the clonogenic potential, migration, invasion, and adhesion was investigated within this study.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting CSCs through the inhibition of glutaminolysis, which is the process of converting glutamine-to-glutamate via the enzyme, glutaminase (GLS), is a promising metabolic interference strategy 431 . GLS1 is associated with different types of cancer, and the GLS1 inhibitor, BPTES, combined with the phosphodiesterase-5 inhibitor, zaprinast, increases the sensitivity of pancreatic CSCs to radiotherapy and promotes apoptosis by increasing the level of intracellular ROS 431 . The first glutaminase inhibitor, DON, was isolated from Peruvian soil and induces apoptosis of breast CSCs 444 .…”
Section: Prospects Of Targeting Cscsmentioning
confidence: 99%
“…Targets of glycolysis include rate-limiting enzymes, transporters, and other complex regulators [428][429][430] . GLUT1, a glucose transporter, has an important role in the maintenance of pancreatic, ovarian, and GBM CSCs 431 . WZB117, a specific GLUT1 inhibitor, successfully inhibits the self-renewal and tumorinitiating capacity of the CSCs in vitro 432 .…”
Section: Targeting Metabolism In Cscsmentioning
confidence: 99%
“…Additionally, it has been suggested that breast cancer cells, in order to maintain the life activities of tumor cells, absorb a lot of glutamate from blood circulation [158]. Studies have shown that glutamate, via activating the alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPAR), as well as promoting breast cancer cell invasion and migration through the activation of the MAPK pathway, could accelerate tumorigenesis [159,160]. In breast cancer, under normoxic conditions, glutamate was also found to enhance the activity of HIF1α [161].…”
Section: Metabolites Of Proteinmentioning
confidence: 99%